Clinicopathological significance of HER2/neu genetic heterogeneity in HER2/neu non-amplified invasive breast carcinomas and its concurrent axillary metastasis. Issue 8 (28th March 2013) - Shafi, Hedyeh; Astvatsaturyan, Kristine; Chung, Fai; Mirocha, James; Schmidt, Michael; Bose, Shikha
Abstract : Background: HER2/neu (HER2) is a significant prognostic marker for breast carcinomas. Recently, new guidelines defining HER2 genetic heterogeneity (GH) were published by the College of American Pathologists. Aims: To determine the prevalence of HER2 GH as defined in primary invasive breast carcinoma, to determine its relationship with prognostic variables and to investigate its impact on concurrent axillary metastasis. Methods: 235 consecutive infiltrating breast carcinomas were evaluated for GH (defined as presence of 5–50% of neoplastic cells with HER2 /CEP17 ratio >2.2) using fluorescence in situ hybridisation. Pathological features of carcinomas with GH were compared with those lacking GH. GH was also evaluated in a subset of 37 paired primary carcinomas and its concurrent axillary nodal metastases using dual in situ hybridisation. Results: HER2 GH was noted in 27% of HER2 negative breast carcinomas. These carcinomas demonstrated aggressive characteristics (larger size, higher grade and greater incidence of lymph node metastasis) in comparison with HER2 negative cases without GH. Higher levels of GH were associated with the equivocal HER2 status. GH was maintained in the concurrent lymph node metastases with some variations; however, two cases with clusters of HER2 amplified cells in the primary carcinoma showed HER2 amplification in the nodal metastasis. Conclusions: HER2 GH is present in 27% of breast carcinomas, portends an aggressive phenotype and contributes to the equivocal HER2 status. Evaluation of the HER2 status in nodal metastasis of select primary carcinomas with GH may be beneficial before treatment selection.